Tall Cell Carcinoma with Reverse Polarity of Breast: Report of a Case with Unique Morphologic and Molecular Features - Mohamed JASSIM; Chennagiri S PREMALATA; Geeta V Patil OKALY; Chunduri SRINIVAS (Türk Patoloji Dergisi, 2021)

(untitled)
Breast carcinomas are a heterogeneous group of malignancy, having variable clinical outcomes depending on their cellular and molecular properties. Tall cell carcinoma with reverse polarity (TCCRP) is a recently described rare entity, which shares morphological features with tall cell variant of papillary thyroid carcinoma but has a distinct morphological, immunohistochemical, and molecular profile. We describe a case of a 40-year-old female patient, who presented with lump in the breast. The patient underwent lumpectomy and was diagnosed as tall cell carcinoma with reverse polarity. Immunohistochemistry and bi-directional Sanger sequencing for IDH2 mutation were used for diagnosis. Tall cell carcinoma with reverse polarity is a rare and newly described entity with characteristic morphological and molecular findings, which carries an excellent prognosis.